Problems Of Training Highly Skilled Gymnasts - Khurozov Gayrat Keldiyorovich (Academia One Publishing, 2023)
In this article provides information about the practical significance of the use of biomechanics, biochemistry, valeology, sports psychology, equipment for organizing and conducting scientific research, in addition to sports theory, in the training of highly qualified gymnasts
Keywords: biomechanics; biochemistry; valeology